A Unique SUMO-2-Interacting Motif within LANA Is Essential for KSHV Latency - Cai, Qiliang (Public Library of Science, 2013)
Kaposi's sarcoma-associated herpesvirus (KSHV) stabilizes hypoxia-inducible factor α (HIF-1α) during latent infection, and HIF-1α reactivates lytic replication under hypoxic stress. However, the mechanism utilized by KSHV to block lytic reactivation with the accumulation of HIF-1α in latency remains unclear. Here, we report that LANA encoded by KSHV contains a unique SUMO-interacting motif (LANA(SIM)) which is specific for interaction with SUMO-2 and facilitates LANA SUMOylation at lysine 1140. Proteomic and co-immunoprecipitation analysis further reveal that the SUMO-2 modified transcription repressor KAP1 is a critical factor recruited by LANA(SIM). Deletion of LANA(SIM) led to functional loss of both LANA-mediated viral episome maintenance and lytic gene silencing. Moreover, hypoxia reduced KAP1 SUMOylation and resulted in dissociation of both KAP1 and Sin3A repressors from LANA(SIM)-associated complex. Therefore, the LANA(SIM) motif plays an essential role in KSHV latency and is a potential drug target against KSHV-associated cancers.